Integrated Character Education (ICE): Reconstructing islamic education policy for sustainable development - Affandy Yusuf; Bunga CItra Lestari; Najwah Addina; Sutrimo Purnomo (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
Nowadays, the flow of information is widespread without spatial and temporal restrictions. This impairs access to information, which can have negative consequences if not used wisely. One of the consequences is the deterioration of students' morale and character. Integrated Character Education (ICE) is an alternative strategic solution to instill global awareness in a young generation. This study analyzes Integrated Character Education (ICE) in the context of Islamic education to reconstruct the direction of educational policies by emphasizing character values ​​as the foundation for sustainable development. The research method uses a qualitative approach through a systematic literature review that analyzes various academic publications and educational policies in the context of Islamic education. The results of the study show that integrating character values ​​into curricula and school programs can promote the development of responsible, cooperative, creative, innovative, and change-minded students. Educational policies that emphasize only cognitive aspects have proven less effective in addressing long-term developmental challenges. For this reason, a policy redesign is needed that emphasizes character development as a central foundation and requires synergies between government, society, and educational institutions. This study contributes to the formulation of an Islamic education policy that is guided by offering instructional implications, including character-based lesson planning, collaborative and reflective learning strategies, and assessment practices that integrate moral values within English and Islamic education to support sustainable development. Keywords: Character building; Islamic Education Policy; Sustainable development; Curriculum development; Inclusive values.